(untitled) (Research, Society and Development, 2020)
Graniferous sorghum (Sorghum bicolor L.) is a cereal strongly used in processed foods because it is gluten free, due to the importance of this grain it is necessary to define safe conditions for storage. Thus, the objective was to determine the desorption isotherms for grains of grain sorghum and to determine the safe water content of storage of this product. The grain desorption isotherms were obtained by the static-indirect method, obtaining the product’s water activity at temperatures of 10, 20, 30 and 40 ºC, for the moisture content range between 14 to 24 ± 0.1 % on dry basis. The mathematical models used to represent the hygroscopicity of agricultural products were adjusted to the experimental data. To verify the degree of adjustment of the models, the magnitude of the coefficient of determination, the Chi-square test, the relative mean error, estimated mean error, Akaike information criteria (AIC), and Schwarz Bayesian information criteria were considered (BIC). All models represent satisfactorily the desorption isotherms, however, according to the evaluated parameters, the Chung-Pfost model was the most appropriate. For the storage of grain sorghum grains the maximum moisture content limit is 15.69; 15.08; 14.53; 14.03% b.s., for temperatures of 10, 20, 30 and 40 ºC, respectively.